Synthesizing personas and scenarios through participatory design to create support systems for academic success of nontraditional students in engineering - Brozina, Cory; Chew, Alanis; Baka, Sarah; Johri, Aditya (Frontiers in Education, 2025)
Increasingly, nontraditional students are becoming a larger proportion of students in engineering and to better support their academic success it is essential to understand their experiences and expectations. This research paper presents the outcomes of a participatory design process conducted with nontraditional students in engineering (NTSE) to synthesize and distill different aspects of NTSE through the development of personas and scenarios. These personas and scenarios will allow stakeholders, such as faculty, advisors, and administration, to better understand how they can support these students. Based on prior preliminary research, a participatory design session (PDS) was held with seven nontraditional engineering student participants who shared their experiences related to support systems in the university. Through this process personas and scenarios were created that provide critical insights into the needs and experiences of non-traditional engineering students. These findings highlight specific areas where existing educational practices can be improved and provide actionable recommendations for enhancing support structures. This work contributes to the development of more inclusive and effective educational environments for nontraditional students in engineering.